Heat shock protein 72 may improve hypotension by increasing cardiac mechanical efficiency and arterial elastance in heatstroke rats. (15th September 2016) - Hsu, Shu-Fen; Chao, Chien-Ming; Chang, Ching-Ping; Lin, Mao-Tsun; Cheng, Bor-Chih
Abstract: Objective: We attempted to test the hypothesis that preinduction of heat shock protein (HSP) 72 in the heart would improve left ventricular performance in rat heatstroke. Methods: Cardiac expression of HSP 72 was quantitatively evaluated by western blot analysis in rats 0 h, 12 h, or 72 h after mild heat preconditioning (MHP; 43 °C for 30 min). They were subjected to severe heat stress (SHS; 43 °C for 70 min) to induce heatstroke. A 1.2 F catheter-tip pressure transducer was inserted into the left ventricle of these group rats under general anesthesia to record hemodynamic in the closed chest with a pressure–volume loop module data recording and analysis system. Results: At the time point of heatstroke onset, compared with normothermic controls, group rats with 12 h post-MHP had significantly increased cardiac HSP 72, decreased hyperthermia, decreased hypotension, decreased bradycardia, increased end-systolic pressure, increased end-diastolic pressure, increased stroke volume, decreased end-systolic volume, decreased end-diastolic pressure, increased cardiac output, increased ejection fraction, increased stroke work, increased arterial elastance, and decreased time constant of fall in ventricular pressure by Glantz-methods. With the loss of cardiac HSP 72 expression observed at 72 h in post-MHP group rats, an insignificant protection against left ventricular performance was observed. Conclusion: Preinduction of cardiac HSP 72 may improve hypotension in heatstroke rats by increasing both cardiac mechanical efficiency and arterial elastance.